Exploring Implications of Brown for Schools of Choice and Raising Academic Standards - Richard A. King; Linda Vogel; Kathryn Whitaker (Educational Considerations, 2004)
After the 1954 Brown v. Board of Education decision, policies designed to comply with the decision were often declared to be unconstitutional.